PENGARUH IKLIM ORGANISASI DALAM MENDORONG PERILAKU INOVATIF MELALUI KREATIVITAS (STUDI KASUS PADA PT. TELKOM (PERSERO) TBK. WITEL MAKASSAR) - Reski Susrini; Mahlia Muis; Wahda Rasjid (Master of Management, Faculty of Economics and Business, Hasanuddin University., 2019)
The study aims to determine the effect of organizational climate on creativity and innovative behavior at PT. Telkom (Persero) Tbk. Witel Makassar either directly or mediation. This study uses a quantitative approach. Finally, the results of this study explain the causal relationship between the variables through hypothesis testing. In this research, analysis method used is path analysis using Smart Partial Least Square (PLS) 2.0 program. The results of this study indicate that partially organizational climate has positive and significant effect on creativity, organizational climate has positive and significant effect on innovative behavior, and creativity has positive and significant effect on innovative behavior. The indirect influence shows that creativity can mediate the organizational climate influence on innovative behavior positively and significantly.